Successful Strategies for Dealing With Infected, Custom-Made Hydroxyapatite Cranioplasty. Issue 5 (July 2018) - Zanotti, Bruno; Zingaretti, Nicola; Verlicchi, Angela; Alfieri, Alex; Parodi, Pier Camillo
Abstract : Abstract: When a cranioplasty implant becomes infected, standard operating procedure dictates its removal and the initiation of a long course of antibiotic therapy. However, removing such a prosthesis can have a series of adverse consequences, including delayed cognitive and motor recovery, lack of brain tissue protection, unsightly deformity, and the need for two additional surgical procedures, not to mention the additional costs involved. To maintain the advantages of cranioplasty, we opted for a conservative approach (levofloxacin and rifampicin every 24 hours for 8 weeks) in a 68-year-old woman whose custom-made porous hydroxyapatite implant, fitted following aneurysm clipping, had become infected. The tissues overlying the implant were curettaged, and the patient's clinical condition, blood markers, and infection course were continuously monitored (local monitoring was performed by single-photon emission computed tomography [SPECT]/computed tomography [CT after intravenous administration of 99m Tc-labeled antigranulocyte antibody). Blood tests and SPECT/CT evidenced a progressive reduction in phlogosis indices and infection locus, even 1 month after antibiotic therapy was commenced, and at 2 years from cranioplasty, the same tests and clinical examination were negative. At 6-year follow-up, clinical assessment revealed nothing out of the ordinary. Hence, specific cases (hydroxyapatite prosthesis, intact dura, cranial CT and magnetic resonance imaging negative for empyema, well-vascularized scalp, antibiotic-responsive bacteria) of infected cranial implant can be treated using a conservative approach consisting of appropriate antibiotic therapy, accompanied by local debridement where necessary, and assiduous monitoring of phlogosis indices and local verification via labeled-leukocyte scintigraphy. Our report, which was compiled after a long-term follow-up period, shows that this conservative procedure appears to be a viable option in cases of infected, custom-made hydroxyapatite cranioplasty, provided that some basic rules concerning clinical and instrumental standards are adhered to, as clearly stated in our report.